Handbook for preclears - "Hubbard, L.Ron" (Copenhagen, 2007)
The Talmud Chronicles is a unique blend of Talmudic events, personalities, and stories of the second century of the common era, bringing to life Jewish law and history in the innovative form of a newspaper from that era. Starting with the unprecedented ousting of Rabban Gamliel as head of the Sanhedrin, and concluding with the revival of the Jewish people in the Galilee, The Talmud Chronicles vividly presents the triumphs and tragedies of this incredible period of time for the Jewish people. With well-founded and authentic portrayals of Roman and Jewish leaders like Trajan, Hadrian, Rabbi Akiva, and Bar Kochba, and through the use of political cartoons, advertisements, and advice columns The Talmud Chronicles adds elements that will be enjoyed by readers young and old.